Mucocutaneous Manifestation of Systemic Lupus Erythematosus Patients At Rheumatology Outpatient Clinic In Dr. Hasan Sadikin General Hospital - Chin Annsha Veimern; Ellyana Sungkar; Hartati Purbo Dharmadji; Laniyati Hamijoyo (Indonesian Journal of Rheumatology, 2017)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune systemic disease which symptoms induced by Ultraviolet rays exposure. It commonly affects women and causes wide range of symptoms. One of the organs affected is mucocutaneous. Our study aims to determine mucocutaneous manifestations of SLE patients in Rheumatology Outpatient Clinic in Dr.Hasan Sadikin General Hospital, Bandung.Methods: A descriptive study with prospective crosssectional design conducted. Data were obtained by interviewing SLE patients as primary data and accessing medical record as secondary data. Ninety-six SLE patients met the inclusion and exclusion criteria wereincluded.Results: From ninety-six subjects, 94.8% subjects are working indoors. Mucocutaneous manifestation were found in most patients. Based on American College of Rheumatology (ACR) criteria, we found mucocutaneous manifestations, such as: oral ulcers in 67 patients(69.8%); malar rash in 63 patients (65.6%); photosensitivity rash in 51 patients (53.1%), and discoid rash erythematous in 21 patients (21.9%). Specific SLE cutanoeus manifestation based on Gilliam classification were found in our study subjects, such as papulosquamous/ psoriasisform (19.5%) , morbilliform (17.7%), vesicobullous annular SCLE (13.5%), annular SCLE (6.3%), and TEN-like LE (1%). Non-specific LE cutaneousmanifestations based on Gilliam classification were also found in our study subjects, such as oral ulcers (69.8%), photosensitivity rash (53.1%), alopecia (86.5%), Raynaud’s Phenomenon (39.6%), nail abnormalities (24.0%), periungual telangiectasia patients (13.5%), vasculitic lesions (12.5%), thrombophlebitis (44.8%), bullous lesion (5.2%) and erythema multiforme (5.2%).Conclusion: Mucocutaneous manifestations in SLE patients based on ACR criteria found most in this study is oral ulcers. Based on Gilliam classification specific LE cutanoeus manifestation was not found in all SLE patients, while non-specific LE mucocutaneous manifestations mostly found is alopecia. Keywords: American College of Rheumatology (ACR) criteria, Gilliam classification, Mucocutaneous manifestations, Systemic Lupus Erythematosus